2015
DOI: 10.1039/c4ra08972c
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and catalytic performance of graphene-reinforced ion-exchange resins

Abstract: The structural and thermal stability of graphene-based polymer nanocomposites were improved with chemical bonded interaction of graphene within the polymer networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Though the catalytic hydration of epoxides has aroused extensive research attention, it still lacks of efficient solid catalysts being able to catalyze the hydration reaction with high glycol selectivity at H 2 O/epoxide ratio less than 5. [2][3][4][5][6][7] Previous studies showed that the silica-based nanoreactor with encapsulated Co (Salen) could catalyze the hydration of epoxides at H 2 O/epoxide ratio around 2 to afford much higher activity and high selectivity than homogeneous counterpart. [8][9] DFT studies suggested that Co(Salen) goes through bi-molecular activation pathway for the hydration of epoxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the catalytic hydration of epoxides has aroused extensive research attention, it still lacks of efficient solid catalysts being able to catalyze the hydration reaction with high glycol selectivity at H 2 O/epoxide ratio less than 5. [2][3][4][5][6][7] Previous studies showed that the silica-based nanoreactor with encapsulated Co (Salen) could catalyze the hydration of epoxides at H 2 O/epoxide ratio around 2 to afford much higher activity and high selectivity than homogeneous counterpart. [8][9] DFT studies suggested that Co(Salen) goes through bi-molecular activation pathway for the hydration of epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…However, this process is an energy extensive process because non‐catalytic hydration process needs a large amount of water for obtaining high glycol selectivity. Though the catalytic hydration of epoxides has aroused extensive research attention, it still lacks of efficient solid catalysts being able to catalyze the hydration reaction with high glycol selectivity at H 2 O/epoxide ratio less than 5 . Previous studies showed that the silica‐based nanoreactor with encapsulated Co(Salen) could catalyze the hydration of epoxides at H 2 O/epoxide ratio around 2 to afford much higher activity and high selectivity than homogeneous counterpart .…”
Section: Introductionmentioning
confidence: 99%
“…1 This exciting new material is a single-atom-thick planar of sp 2 -bonded carbon atoms perfectly arranged in sixmembered rings. Owing to its extraordinary physical, chemical and structural properties, [2][3][4][5][6][7][8][9] graphene has quickly sparked great interest across many disciplines, including highfrequency electronics and nano-electronics, [10][11][12][13][14] energy storage and conversion, [15][16][17][18][19][20] field emission display, 21,22 and bioscience/biotechnology because of its unique physicochemical properties. [23][24][25][26] Graphene and its derivatives play an ever-increasing role in the area of bioanalysis and biomedicine.…”
Section: Introductionmentioning
confidence: 99%